Promoting Entrepreneurship Spirit at the Upper Primary School - Vaidya, Shipra (INDIAN EDUCATIONAL REVIEW, 2009)
The present study is an exploration of our understanding of entrepreneurial construct among elementary stage students (age groups 11-14 years) and carves out the ways to create and strengthen the entrepreneurial culture within the school setting. The study aims to profile entrepreneurship as an educational objective and help children grasp the concept while fostering their enterprise/entrepreneurial skills along the way.